Population-based norms for the Cervantes-SF short-form questionnaire assessing health-related quality of life in menopause. (April 2021) - Coronado, Pluvio J.; Monroy, Manuel; Fasero, María; Sánchez-Borrego, Rafael; Palacios, Santiago; Rejas, Javier; Ruiz, Miguel A.; ,
Highlights: The Cervantes-SF scale is designed to measure health-rate quality of life (HRQoL) in peri- and post-menopausal women. HRQoL norms are a key attribute to interpret patient's health either from a clinical perspective and health decision maker as well. This work was designed to develop population norms for Cervantes-SF for the first time. These results support the validity of the Cervantes-SF scale as valid instrument for measuring the impact of menopause on HRQOL. The norms obtained facilitate the interpretation of these scores in clinical practice, research, and health management. Abstract: Objectives: To develop the population-based norms for the Cervantes-SF scale, which measures the impact of menopause on the health-related quality of life (HRQOL) of women in Spain. Methods: We used a sample obtained from representative studies of the Spanish population according to geographic density and autonomous community. This sample was composed of 5, 237 non- institutionalized peri- and post-menopausal women, aged 40−75 years. Measures of central tendency, dispersion and percentiles were calculated for the total score and its dimensions, in 11 three-year age categories. Construct validity was analyzed based on a comparison with known groups to confirm the validity of the normative scales. Results: The norms show a monotonic gradient, with an incremental impact on HRQOL as age increases, as shown by an increase in the total score and each of the dimensions. Fifty percent of women showed that peri-/post-menopausal symptomatology interfered with HRQOL > 39 %, ranging from 25 % (40−44 years) to 47 % (72−75 years). The population norms showed significant differences between groups according to generic HRQOL, number of comorbidities, history of osteoporotic fracture, educational level, and presence of obesity. Conclusions: These results support the validity of the population-based norms for the Cervantes-SF scale, a valid instrument for measuring the impact of menopause on HRQOL in Spain. The norms obtained facilitate the interpretation of these scores in clinical practice, research, and health management.